2016
DOI: 10.1515/opli-2016-0013
|View full text |Cite
|
Sign up to set email alerts
|

Narratives of Belonging in the Digital Diaspora: Corpus Approaches to a Cultural Concept

Abstract: Abstract:In this study, I examine narratives of belonging through a corpus of digital diasporic discourse. The corpus is based on a Nigerian online discussion forum; its users primarily consist of both local Nigerians and members of the globally dispersed Nigerian diaspora. The study sets out by providing a working definition of narratives of belonging couched in the sociolinguistic tradition of approaching narrative structures. This includes aspects of personal narration, structural features, and reference to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…It explores the resemiotized contexts and chronotopic properties that are indicative of such narratives. In this regard, the notion of "digital diaspora" as an emerging phenomenon of diasporic and transnational communication (Heyd 2016) is central to the current discussion. Data collection started in September 2021 and continued until September 2022.…”
Section: Methodsmentioning
confidence: 99%
“…It explores the resemiotized contexts and chronotopic properties that are indicative of such narratives. In this regard, the notion of "digital diaspora" as an emerging phenomenon of diasporic and transnational communication (Heyd 2016) is central to the current discussion. Data collection started in September 2021 and continued until September 2022.…”
Section: Methodsmentioning
confidence: 99%
“…The results obtained show that vloggers have universal feelings like fears and culturally specific ones like mask-wearing related while inviting their viewers to construct their emotional experience revealing a new form of migrant identity and its role in delivering healthrelated information in this crisis. Moreover, Heyd (2016) defines an important notion for understanding digital diaspora: narratives of belonging. The author argues that this concept brings together two evocative notions: storytelling "as a fundamental human activity and linguistic act of identity" and belonging "as a category that is relevant to all explorations to all human experience in societies marked by globalization and mobility".…”
Section: Disinformation and Diaspora Related Researchmentioning
confidence: 99%
“…The author argues that this concept brings together two evocative notions: storytelling "as a fundamental human activity and linguistic act of identity" and belonging "as a category that is relevant to all explorations to all human experience in societies marked by globalization and mobility". For this notion, Heyd (2016) identifies four criteria when analyzing diaspora text: personal narratives, i.e., reflecting an episode that is personalized and related to a lived individual experience, account of events, reference to components embedded in the notion of belonging, and evaluation through, e.g., critical positioning towards narrated events. Kozachenko (2018) Based on the comprehensive review conducted in this research it can be concluded that while different dimensions of the ongoing conflict between Russia and Ukraine are tackled through different studies, e.g., annexation of Crimea, Euromaidan, and current events, still limited studies are dedicated to understanding diaspora's role in relation to disinformation propagation in social media.…”
Section: Disinformation and Diaspora Related Researchmentioning
confidence: 99%
“…Words and phrases that were used as synonyms for dusha included: internal contradiction and contradictory things, life, hope, conscience, sincerity, music, Russian language, intuition, fluency in culture and habits, interest, the unconscious, friendship, love, compassion and kindness (Pesmen 2000: 311-312). Words or concepts can play a role in narrating and constructing belonging (Heyd 2016), and when this is done in a specific place, the use of a word speaks not only about that place itself, but also about how something might be missing from the surrounding society.…”
Section: Building Groupness By Mobilising Affective Conceptsmentioning
confidence: 99%